Inter‐hemispheric connectivity in the fusiform gyrus supports memory consolidation for faces. (16th March 2016) - Geiger, Maximilian J.; O'Gorman Tuura, Ruth; Klaver, Peter
Abstract: This study investigated how changes of functional connectivity over time accompany consolidation of face memories. Based on previous research, it was hypothesized that connectivity changes in networks initially active during face perception and face encoding would be associated with individual recognition memory performance. Resting‐state functional connectivity was examined shortly before, shortly after and about 40 min after incidental learning of faces. Memory performance was assessed in a surprise recognition test shortly after the last resting‐state session. Results reveal that memory performance‐related connectivity between the left fusiform face area and other brain areas gradually changed over the course of the experiment. Specifically, the increase in connectivity with the contralateral fusiform gyrus, the hippocampus, the amygdala and the inferior frontal gyrus correlated with recognition memory performance. As the increase in connectivity in the two final resting‐state sessions was associated with memory performance, the present results demonstrate that memory formation is not restricted to the incidental learning phase but continues and increases in the following 40 min. It is discussed that the delayed increase in inter‐hemisphere connectivity between the left and right fusiform gyrus is an indicator for memory formation and consolidation processes. Abstract : Sessions of resting‐state fMRI were recorded before and two times after participants performed an incidental learning task with pictures of faces. We show that later assessed recognition memory performance was associated with resting‐state functional connectivity networks of a seed region in the fusiform faces area before learning and with changes of functional connectivity after learning. The contralateral fusiform gyrus, the hippocampus, the amygdala and the inferior frontal gyrus were involved. Notably, delayed increase in connectivity with the contralateral fusiform gyrus was associated with recognition memory performance.